2014
DOI: 10.1002/htj.21140
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Natural Convection in an Enclosure with an Internal Heat Source at Higher Rayleigh Numbers

Abstract: Natural convection is extensively used in cooling of large scale electrical and electronic equipments. This work involves study of flow and heat transfer characteristics in enclosures with partial openings having an internal heat source at higher Rayleigh number (Rah > 106). It involves the numerical simulation of 2D steady state natural convection in enclosures of different aspect ratios (H/W = 2 and 3) for five Rayleigh numbers (Rah = 107, 108, 109, 1010, and 1011). Two different configurations have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Sinusoidal type of variations in heat with Ra=10 5 . Natural convection studies in enclosures with vents and internal heat source at high Rayleigh number (Ra>10 6 ) has been analyzed by Gowrishankar [25]. They observed that with increase in Ra, flow becomes more fluctuating and moves towards chaotic regime.…”
Section: Introductionmentioning
confidence: 99%
“…Sinusoidal type of variations in heat with Ra=10 5 . Natural convection studies in enclosures with vents and internal heat source at high Rayleigh number (Ra>10 6 ) has been analyzed by Gowrishankar [25]. They observed that with increase in Ra, flow becomes more fluctuating and moves towards chaotic regime.…”
Section: Introductionmentioning
confidence: 99%